2011
DOI: 10.3892/ijo.2011.1225
|View full text |Cite
|
Sign up to set email alerts
|

Purified cranberry proanthocyanidines (PAC-1A) cause pro-apoptotic signaling, ROS generation, cyclophosphamide retention and cytotoxicity in high-risk neuroblastoma cells

Abstract: Abstract. Optimized purification of oligomeric proanthocyanidines (PAC) from cranberry generated PAC-1A which selectively affected the viability of various neuroblastoma (NB) cell lines representing a spectrum of high-risk NB features. PAC-1A caused a loss of mitochondrial transmembrane depolarization potential (∆Ψm) and increased generation of reactive oxygen species (ROS) which was directly correlated to the modulation of apoptotic marker proteins in SMS-KCNR cells. PAC-1A reduced the expression of pro-survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…This gene is also reported to inhibit chemotherapy induced apoptosis [72]. Inhibition of bcl-xl both at transcriptional and translational levels by TCE is in line with findings with other natural products showing anticancer properties, like curcumin, andrographolide, and proanthocyanidines [73,74]. Annexin V-FITC/PI staining study further supported this observation as there was increase in early apoptotic cell population which may be due to the induction of differentiation in C6 glioma cells that led cells to undergo programmed cell death.…”
Section: Discussionsupporting
confidence: 72%
“…This gene is also reported to inhibit chemotherapy induced apoptosis [72]. Inhibition of bcl-xl both at transcriptional and translational levels by TCE is in line with findings with other natural products showing anticancer properties, like curcumin, andrographolide, and proanthocyanidines [73,74]. Annexin V-FITC/PI staining study further supported this observation as there was increase in early apoptotic cell population which may be due to the induction of differentiation in C6 glioma cells that led cells to undergo programmed cell death.…”
Section: Discussionsupporting
confidence: 72%
“…Anti-apoptotic functions of bcl-xl are well known. Recent reports on curcumin, andrographolide, cranberry proanthocyanidines have established bcl-xl mediated pro-apoptotic properties of natural compounds [52], [53]. Therefore we evaluated whether ASH-WEX could influence bcl-xl expression in the IMR-32 cells.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, the SAAE increased the production of ROS, which may have triggered the dysfunction in mitochondrial membrane potential and apoptotic cell death observed in melanoma cells. Singh et al [69] showed that proanthocyanidins extracted from cranberries have a cytotoxic effect on neuroblastoma cells by increasing ROS production and depolarizing the mitochondrial membrane potential. Furthermore, other extracts and natural compounds have already been described as promising in cancer treatment because they increase ROS and depolarize the mitochondrial membrane potential [70,71,72,73].…”
Section: Discussionmentioning
confidence: 99%